(untitled) (Tawshiyah: Jurnal Sosial Keagaman dan Pendidikan Islam, 2020)
Learning activities in the Administrator Leadership Training (PKA) is a system in which there are learning components. The learning components are training participants, lecturers, learning objectives, material / content, methods, media and evaluation. The learning process for this Administrator Leadership Training is carried out through the learning process with the classical method, namely the learning process face-to-face in the learning room between the Lecturer and the training participants, but during the Covid-19 pandemic the learning process was transferred to non-classical learning using the Distance Learning method. (Distance Learning) where participants and lecturers do not meet face to face in a learning room. The method of Learning Distance Learning (Distance learning) is carried out by utilizing information technology (IT), between the Lecturer and the training participants. One of the learning components as mentioned above is the learning media component which functions the same as other components in the process of achieving the learning objectives of the Administrator Leadership Training course. Lecturer as the instructor of the Administrator Leadership training in the learning process using classical methods and Distance Learning methods using learning media. Through this paper, we will describe the function of learning media using the Distance Learning Adminstrator Leadership Training method. With the elaboration of the learning media’s function, it is hoped that Lecturer as the instructor of the administrator leadership training course will always use and develop learning media in delivering the training subject material that she teaches, so that the learning objectives of the training course and the objectives of the Administrator Leadership training are maximally achieved.